PERAN PENYULUH AGAMA SEBAGAI MEDIATOR NON AJUDIKASI TERHADAP PIHAK SENGKETA - Asiqah, Laili; Syamhari, Hari; Fatimah, Siti (LP2M of Institute for Research and Community Services - UIN Walisongo, 2018)
Courts are not the only media to resolve cases for the parties to the dispute. There are still other ways out of court that are actually more appropriate and quick to resolve cases of dispute and / or crime, is mediation. In the Religious Courts have also been introduced to mediation to further enhance the peace efforts that have been undertaken to improve broken family relationships (want to separate / talaq). One of the alternatives presented in solving a divorce case is based on a win-win solution. The problem to be studied in this article is how the duties and responsibilities of religious instructors in carrying out their profession to provide advocacy, mentoring, and mediate non ajudikasi based on the principle of help-help, cling to the source of Islamic teachings. Second, the role of religious counselor in the mediation of divorce dispute cases should be competent, so that no party is harmed.Â Pengelolan Pengadilan bukan satu-satunya media untuk menyelesaikan perkara bagi para pihak yangbersengketa. Masih ada cara lain di luar pengadilan yang sebenarnya lebih tepat dan cepat untukmenyelesaikan kasus sengketa dan atau kriminal, yaitu mediasi. Di PengadilanAgama juga telah diperkenalkan dengan mediasi guna lebih meningkatkanupaya-upaya damai yang selama ini dijalankan untuk memperbaiki hubungankeluarga yang sedang retak (ingin berpisah/talaq).Salah satu alternatif yang disuguhkan dalam menyelesaikan perkara perceraian adalah berdasarkan pada konsep sama-sama menang (win-win solution). Permasalahan yang akan dikaji dalam artikel ini adalah bagaimana tugas dan tanggung jawab penyuluh agama dalam menjalankan profesinya untuk memberikan advokasi ,pendampingan, dan menjadi mediator non ajudikasi berdasarkan pada prinsip tolong-menolong, berpegang teguh pada sumber ajaran agama Islam. Kedua, peran penyuluh agama dalam mediasi perkara sengketa perceraian sebaiknya harus kompeten, sehingga tidak ada pihak yang dirugikan.